Estrategias de gestión del talento humano en Mipymes sector diseño y su incidencia en la competitividad (2018)
“MSMEs in Colombia occupy 92% of the business structure of the country”, that is, they have a large percentage of contribution to the national economy, which is why it was decided to make a study regarding the competitiveness of the same seeking to know what factors would ensure the permanence in the market and ensure its growth. Consulting relevant authors on the subject, it was found that the four determining factors in the competitiveness of MSMEs are: Human Talent, Innovation, Technology and Research and Development; organized respectively in order of relevance.